Edmodo mobile: developing e-module biology cell for online learning community - Nuril Hidayati; Ardian Anjar Pangestuti; Trio Ageng Prayitno (Universitas Negeri Jakarta, 2019)
The results of observations on learning cell biology show that most students assume that cell biology is a complex and abstract material. The level of conceptual understanding is still relatively low which can be observed from the low test results. There is a misconception that cell structure is a dense and non-porous structure; this can be seen in the results of student drawings on the topic of cell membranes. One solution to overcome the above problem is to develop contemporary teaching materials in the form of e-module based on Edmodo android so that students can easily access them using only a smartphone. The research objective was to develop an Edmodo android cell biology module. This type of research was research and development (R&D). The development model used is Thiagarajan 4D, which is defined, design and develop. The instruments used were the e-module validation questionnaire by experts (material experts, media experts, and practitioners) and the e-module feasibility test questionnaire on 24 students. Research data were a score of validation results and other supporting information to perfect the e-module. As a result, the Edmodo Android of cell biology based that has been developed through Thiagarajan 4D has valid criteria. Thus, it can be used in cell biology learning.